Treating rheumatoid arthritis to target: Russian version of international guidelines for patients - Evgenia Vladislavovna Orlova; D E Karateev; N A Bulgakova (Научно-практическая ревматология)
Objective: to assess how the Russian version of the international «treat-to-target» (T2T) recommendations can be understood by patients with rheumatoid arthritis (RA) and the extent to which they consent to their content. Material and methods. At Stage 1, the principles and recommendations of the international T2T version for patients were translated into Russian and agreed upon by the Russian Federation's Working T2T Expert Group members and one patient. At stage 2, the project was discussed and edited at a one-day conference with the participation of 15 RA patients (11 women and 4 men at the age of 28 to 64 years) from 6 regions of Russia. Consensus on its final version was achieved. At stage 3, eighty-six RA patients (77 women and 9 men at the age of 20 to 72 years with a disease duration of 3 months to 18 years) from 7 Russian regions (including 75.6% from the Central Federal District) assessed the clarity of translation of each principle (A-D) and each recommendation (1-10) into an unprofessional language and the degree of consent to its content, by using the 10-point Likert scale (0 = strongly disagree; 10 = strongly agree). Results. The consent of the patients to the translation and content of the T2T principles and recommendations was more than 8.7 scores. The mean level of translation clarity into the unprofessional language was 9.41 scores (from 8.82 scores for Recommendation No. 6 to 9.88 scores for Recommendation No. 10), that of consent to the content was 9.34% scores (from 8.76 scores for Recommendation No. 4 to 9.79 scores for Recommendation No. 10). The minimum level of consent was observed for Recommendations No. 3 (low disease activity as an alternative to remission) and No. 4 (drug therapy reconsideration frequency) was 8.85 and 8.76 scores, respectively. The consent to the content of Recommendation No. 3 was lower in the very early and early stages of the disease (7.93 scores) and higher in the extended and late stages (9.6 scores). In young patients aged 20 to 40 years, the consent to Recommendation No. 4 was higher (9.54 scores) and in those aged 41 to 72 years, that was lower (8.31 scores). There were no differences in the perception of the recommendations, depending on the level of education. The maximum level of consent to General Principle No. 1 (joint decision with a patient about treatment) and Recommendation No. 10 (patient awareness of the treatment goal and its achievement strategy) was 9.73 and 9.79 scores, respectively. Conclusion. There is a high level of consent to the content of the principles and recommendations of the Russian T2T version for patients. The content to Recommendation No. 3 increases with longer disease duration and that to Recommendation No. 4 decreases with age. In the future, it is necessary to assess a relationship between the degree of consent and the T2T recommendations and geographical indications and to reveal associations and differences in the perception of the recommendations among physicians and patients. This approach is able to remove obstacles to introduce the T2T initiative in real clinical practice and to optimize the results of RA treatment.